Mineral Possibilities of Baffin Island - E. H. Kranck (Canadian Institute of Mining, Metallurgy and Petroleum, 1951)
Introduction Baffin Island is still too in-accessible to be of interest to the mining industry. However, twenty years ago few people dreamed of mining iron ?ore in Labrador. A journey by air to the most remote places in the Arctic is today no more remarkable than a trip to Europe, and the technical difficulties of mining minerals of high value are not insurmountable. Some ?observations concerning the geology and mineral possibilities of Baffin Island, the largest of the Arctic islands, may therefore interest the members of the Institute, in spite of problematic practical value of the subject. The following short account is mainly based on observations made during the Baird Expedition of the Arctic Institute of North America last summer 1950), and on information available from earlier expeditions. Early Work Baffin Island was one of the first parts of Canada to attract prospectors. Frobisher sent a shipload of rocks, which he believed contained precious metals, from Baffin Island to England. This attempt, however, was a failure and no further serious prospecting work has, so far as I know, been done. During the past few years geological mapping has been carried out by the Geological Survey of Canada (Fortier. Davison, 1949-1950) in the southern parts ?of the island, along the coast of Hudson strait. In 1942, Weeks mapped the coast from Pangnirtung to the head of Cumberland fiord, and Netteling river up to Netteling lake. In the northern parts of the island, only scattered observations have been made ?by Bell, Watkins, Baird, and others.